1990
DOI: 10.1016/0014-5793(90)80074-s
|View full text |Cite
|
Sign up to set email alerts
|

Mastoparan inhibits phosphoinositide hydrolysis via pertussis toxin‐intensive G‐protein in human astrocytoma cells

Abstract: Mastoparan inhibited PH]inositol phosphate accumulation induced by carbachol as well as cyclic AMP accumulation induced by isoproterenol in 1321Nl human astrocytoma cells. Mastoparan inhibited GTPyS-induced, but not Caz+-induced, PH]ino sitol phosphate accumulation in membrane preparations with an K,, of approximately IO pM. The inhibitory effect of mastoparan on carbachol-induced fH]inositol phosphate a~umulation was resistant to pertussis toxin (IAP) reagent in intact cells. These results suggest that mastop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…6). Incubating the cells for 5 h in 1 µM mastoparan, which can either activate G-protein dependent mechanisms (Higashijima et al 1988) or inhibit some pertussis toxin-insensitive Gprotein activation of phosphoinositide hydrolysis in human astrocytoma cells (Nakahata et al 1990), did not alter or mimic histamine´s action (n=4) (Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…6). Incubating the cells for 5 h in 1 µM mastoparan, which can either activate G-protein dependent mechanisms (Higashijima et al 1988) or inhibit some pertussis toxin-insensitive Gprotein activation of phosphoinositide hydrolysis in human astrocytoma cells (Nakahata et al 1990), did not alter or mimic histamine´s action (n=4) (Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…Because it has been revealed that mastoparan directly activates G i/o in a pertussis toxin-sensitive manner, mastoparan has been assumed to be a G-protein activator (Higashijima et al, 1988). We have demonstrated previously that mastoparan suppressed phosphoinositide hydrolysis induced by the muscarinic receptor agonist carbachol in 1321N1 human astrocytoma cells (Nakahata et al, 1990). Likewise, Wojcikiewicz and Nahorski (1989) showed that mastoparan inhibited phosphoinositide hydrolysis induced by guanosine 5Ј-O-(3-thio)triphosphate in permeabilized SH-SY5Y human neuroblastoma cells.…”
mentioning
confidence: 77%
“…3 H]inositol phosphates as described previously (Nakahata et al, 1990). In brief, PC-12 cells were cultured in 12-well plates at the density of 2.0 ϫ 10 5 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…18 The ability of mastoparan to penetrate membranes and activate G proteins in intact cells has been demonstrated in mast cells, 12 pulmonary artery endo-thelial cells, 19 and human astrocytoma cells. 20 In phospholipid bilayers, mastoparan exhibits a greater affinity for d and G o than for G,, 9 although the affinity for G q proteins has not been examined. In the current experiment, pertussis toxin treatment at a concentration that ADP ribosylates endogenous G proteins in intact vascular preparations 21 did not affect the contractile response to mastoparan, so the G protein activated in vascular smooth muscle cells does not appear to be G, or G o .…”
Section: Discussionmentioning
confidence: 99%